Health Education about Healthy Sleep Patterns at the Aisyiyah Orphanage - Nurhanifah, Dewi; Aulia, Nazi Ratul; Agim, Agim; Basri, Ahmad Hasanul; Ayu E., Chinta Kartika; Astuti, Elsi; Norkhaliza, Fitria; Fitriana, Fitriana; Maulana, Iqbal (UrbanGreen Central Media, 2023)
Sleep is basic needs for every human being and it has an important role in children's development. Sleep not only has an impact on physical and emotional development, but is also closely related to cognitive function, learning and attention (Liu et al., 2005). A good and regular sleep pattern can have a good effect on health (Guyton and Hall, 2012). Health education with the title